Comparative analysis of complete chloroplast genome sequences of two tropical trees Machilus yunnanensis and Machilus balansae in the family Lauraceae - Song, Yu; Dong, Wenpan; Liu, Bing; Xu, Chao; Yao, Xin; Gao, Jie; Corlett, Richard T. (Frontiers in Plant Science, 2015)
Machilus is a large (c. 100 spp.) genus of trees in the family Lauraceae, distributed in tropical and subtropical East Asia. Both molecular species identification and phylogenetic studies of this morphologically uniform genus have been constrained by insufficient variable sites among frequently-used biomarkers. To better understand the mutation patterns in the chloroplast genome of Machilus, the complete plastomes of two species were sequenced. The plastomes of M. yunnanensis and M. balansae were 152, 622 bp and 152, 721 bp respectively. Seven highly variable regions between the two Machilus species and three of them between Machilus and Cinnamomum were identified and 297 mutation events, including one micro-inversion in the ccsA-ndhD region, 65 indels, and 231 substitutions, were accurately located. Thirty-six microsatellite sites were found for use in species identification and 95 single-nucleotide changes were identified in gene coding regions.